PH

A=\(\frac{N+4}{N-1}\left(n\inℤ\right)\)

B=\(\frac{2n+4}{n-1}\left(n\inℤ\right)\)

PL
30 tháng 6 2019 lúc 22:16

\(A=\frac{n+4}{n-1}=\frac{n-1+5}{n-1}=1+\frac{5}{n-1}.\)

\(\Rightarrow A\in Z\Leftrightarrow\frac{5}{n-1}\in Z\Rightarrow n-1\inƯ_5\)

Mà \(Ư_5=\left\{\pm1;\pm5\right\}\)\(\Rightarrow...\)

\(B=\frac{2n+4}{n-1}=\frac{2n-2+6}{n-1}=2+\frac{6}{n-1}\)

\(\Rightarrow B\in Z\Leftrightarrow\frac{6}{n-1}\in Z\Rightarrow n-1\inƯ_6\)

Mà \(Ư_6=\left\{\pm1;\pm2;\pm3\right\}\Rightarrow...\)

Bình luận (0)